MAKNA RINGGET GAMBI MULI PILANGAN DALAM PENDEKATAN STILISTIKA - Santo, Riko; Amiliadi, Amiliadi (FKIP Universitas Lampung, 2025)
This research is about the meaning of Ringget Gambi Muli Pilangan in stylistic studies. The formulation of the problem of